Performance verification of methodology for determination of nitrate ion in drinking water samples - Ribeiro, Beatriz Galdino; David, Paulo Roberto de Barros Salomão; Daltro, Tatiana Pinto Pereira; Charamba, Lívia Vieira Carlini; Andrade, Marcelo Farias de; Napoleão, Daniella Carla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
Contaminated water is one of the main public health risks. One way to assess its quality is by quantifying nitrate through ultraviolet (UV) spectrophotometry. In this work, the performance of the UV spectrophotometric method for nitrate ion determination in water was studied, with linearity, precision, accuracy, limit of detection (LOD), limit of quantification (LOQ) and robustness being verified. In the working range studied (5.0-25.0 mgN·L-1), all validation parameters are in accordance with the acceptance criteria established by INMETRO. In linearity, the value of r (0.999) was higher than the criterion (0.995). In the study of precision and accuracy, the coefficients of variation for repeatability and intra-laboratory reproducibility were 1.79 and 2.34%, and 1.44 and 2.52%, respectively (<5%). The value of the relative error (15.8 and 8.1%) was also lower than the criterion (≤ 20%). The LOD and LOQ obtained were 0.56 and 1.70 mgN·L-1, respectively. In the evaluation of the robustness no factor had a significant effect on the final result. Analyzing real samples, the percentages of recovery were between 88.5 and 103.6%, according to the established criteria (80-110%). In this way, it can be said that the method presents reliability to the intended purpose.